2013
DOI: 10.1177/0284185113481698
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid sinus diverticulum and pulsatile tinnitus: analysis of CT scans from 15 cases

Abstract: Dehiscent sigmoid plate and extensive temporal bone pneumatization are two important imaging characteristics of the PT induced by sigmoid sinus diverticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…Previous literature reported that the SSD was usually located on the superior curve and/or the descending segment of the sigmoid plate. 1,5 Data from the present study were similar: the upper and lower segments were most frequently involved in the PT group, whereas the lower segment was most frequently involved in the non-PT group. The interobserver reliability for location of SSD was high.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous literature reported that the SSD was usually located on the superior curve and/or the descending segment of the sigmoid plate. 1,5 Data from the present study were similar: the upper and lower segments were most frequently involved in the PT group, whereas the lower segment was most frequently involved in the non-PT group. The interobserver reliability for location of SSD was high.…”
Section: Discussionsupporting
confidence: 66%
“…Most scholars suggest that the incomplete sigmoid plate promotes the transmission of venous hum from the vessels to the cochlea. 1,2,5 SSD, however, is also found in patients without PT. 6 Schoeff et al 2 reported two non-PT patients with evidence of SSD on CT images (1.2% of patients).…”
Section: Introductionmentioning
confidence: 90%
“…Three main theories have been proposed for the mechanism of SSDD, the idiopathic intracranial hypertension (IIH) theory [5], blood flow impacting theory [6,3,5], and osteoporosis theory [7]. According to the blood flow impacting theory, SSDD is caused Liu Zhaohui and Dong Cheng contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…In the osteoporosis theory, SSDD is considered an early manifestation of osteoporosis in the elderly. However, the majority of SSDD cases presenting with PT are young or late middle-aged people, making these two theories unlikely [5,6,8]. The IIH theory is based on the marked female preponderance in both SSDD and IIH patients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Various imaging strategies have been proposed and continue to evolve to investigate the causes of PT. Compared with promising results from dual-phase contrast-enhanced computed tomography (DP-CECT), which has the advantage of demonstrating artery, venous, soft tissue, and temporal bone in a single study, 27 high-resolution CT (HRCT) and magnetic resonance imaging (MRI) used in previous studies have limitations.…”
Section: Introductionmentioning
confidence: 99%